Engaging Young EFL Learners Through English Monopoly - Firslady Dolopo; Lestari Setyowati (Linguista: Jurnal Ilmiah Bahasa, Sastra, dan Pembelajarannya, 2025)
Vocabulary learning is a fundamental component of early English as a Foreign Language (EFL) instruction, providing the foundation for young learners’ communicative competence. To support vocabulary acquisition, instructional approaches should be concrete, engaging, and developmentally appropriate. This study aimed to develop an interactive English Monopoly-based board game for Grade 1 EFL learners and examine its feasibility and classroom reception. A Research and Development (R&D) approach guided by the ADDIE instructional design framework was employed, functioning as a design model rather than a research method. The instructional media was developed through the stages of analysis, design, development, implementation, and evaluation. Data were collected through expert validation, classroom observations, student response questionnaires, and teacher feedback forms. The study adopted a descriptive qualitative approach supported by descriptive quantitative data, focusing on feasibility, usability, and user responses. The findings indicate that the board game is a feasible instructional medium, fostering high levels of student enjoyment, motivation, engagement, collaboration, and active participation. These results highlight the potential of physical, game-based media to support interactive vocabulary learning in early EFL classrooms.